Pengaruh PENGARUH ABRASI PANTAI TERHADAP KETAHANAN SOSIAL MASYARAKAT PESISIR DESA LIMBANGAN KECAMATAN ULUJAMI KABUPATEN PEMALANG - Nikmah, Zulfatun; Zulfa, Nely; Syah Putra, Rizal Ichsan (Jounal of Enviromental Science Sustainable, 2024)
THE EFFECT OF COASTAL ABRASION ON THE SOCIAL RESILIENCE OF COASTAL COMMUNITIES IN LIMBANGAN VILLAGE, ULUJAMI, PEMALANG By Zulfatun Nikmah (3719110016) A maritime country is a country with a larger water area than land. Indonesia is one of the maritime countries with the longest coastline in the world. Climate change has a significant impact on coastal areas, as it can lead to coastal erosion. This study aims to determine the impact of coastal erosion on the social resilience of the coastal community in Limbangan Village, Ulujami District, Pemalang Regency. The research design used in this study is The Explanatory Design, which aims to explain the causal relationship between the phenomenon of coastal erosion and the social resilience of coastal communities. Primary data was collected through questionnaires distributed to coastal residents and supported by secondary data from various sources. The research findings concluded that the greater the coastal damage caused by erosion, the greater the resulting impact, thereby reducing the community’s ability to recover from post-disaster conditions. However, the overall enhancement of social resilience can essentially be achieved through the strengthening of development across nine elements of community social resilience. Keywords: Coastal erosion, explanatory design, social resilience, maritime